Extended algorithm to construct a quadtree from Freeman chain code in four directions - Nerat, Andrej; Strnad, Damjan; Zupančič, Eva; Žalik, Borut (Image Analysis and Stereology, 2019)
This paper introduces improvements to the algorithm that was proposed in 2001 by Chen and Chen. The algorithm constructs a quadtree directly from Freeman chain code in four directions. We have improved the algorithm in two ways: Firstly, a time efficient solution using the space filling Z-order curve is proposed for a self-intersection case that was not considered by Chen and Chen. Secondly, the algorithm is expanded to handle geometric objects containing holes. The computational efficiency of the extended algorithm was confirmed by the experiments.